2012
DOI: 10.1037/a0026261
|View full text |Cite
|
Sign up to set email alerts
|

Action-specific effects in a social context: Others' abilities influence perceived speed.

Abstract: According to the action-specific account of perception, perceivers see the environment relative to their ability to perform the intended action. For example, in a modified version of the computer game Pong, balls that were easier to block looked to be moving slower than balls that were more difficult to block (Witt & Sugovic, 2010). It is unknown, however, if perception can be influenced by another person's abilities. In the current experiment, we examined whether another person's ability to block a ball influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 67 publications
3
30
0
Order By: Relevance
“…In another study, the computer's performance was not perfect and corresponded to the paddle size. Again, the paddle size did not affect the apparent ball speed (Witt, Sugovic, & Taylor, 2012). These four studies have revealed uniquely disconfirmatory predictions.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…In another study, the computer's performance was not perfect and corresponded to the paddle size. Again, the paddle size did not affect the apparent ball speed (Witt, Sugovic, & Taylor, 2012). These four studies have revealed uniquely disconfirmatory predictions.…”
mentioning
confidence: 77%
“…When watching another human play, paddle size continues to influence the estimated ball speed (Witt, South, & Sugovic, 2014;Witt, Sugovic, & Taylor, 2012). When watching another person, the perceiver is theorized to simulate how the perceiver would do if placed in the actor's situation.…”
Section: Pitfall #1: Uniquely Disconfirmatory Predictionsmentioning
confidence: 99%
“…As another empirical example, when playing a classic Pong game on a computer, participants perceive the speed of the virtual ball to be faster when using a smaller (vs. bigger) Psychological Research paddle and when they observe another use a smaller paddle, but not when observing a computer use a smaller paddle, even when the computer was error prone simulating human movement (Witt, Sugovic, & Taylor, 2012). Moreover, participants who first play the Pong game and then observe another play the game experience the speed of the virtual ball in terms of their own action capabilities (i.e., movement-effect memories).…”
Section: Introductionmentioning
confidence: 98%
“…This concept is useful for explaining emergence of interpersonal interactions in team sports since the ability to perceive action possibilities for self in humans is complemented by their capacity to perceive another individual's affordances [22] and intentions [23]. As Gibson argued, the richest affordances are provided by interactions with others, since ‘behavior affords behavior’ (p135), signifying how the environment itself can also be perceived in relation to self and another person's abilities (see Witt et al [24], [25]). Accordingly, an ecological dynamics approach advocates that the interpersonal synergies [26] established between system agents in sports teams can emerge through the perception of shared affordances .…”
Section: Introductionmentioning
confidence: 99%